The effect of gentiopicroside on brain tissue repair in mice during the acute phase of middle cerebral artery occlusion - Ling Kui; Guoyun Wang; Li Zhang; Qifeng Liao; Xi Li; Shuangshuang Wang; Tao Chen; Bingfeng Leng; Jinqun Huang; Yinming Jiao; Qiaoyuan Ye; Qingqian Zeng; et al. (Molecular Biology Reports, 2026)

Heterogeneous driving mechanisms of urban-rural residential carbon emissions in severe cold agro-pastoral ecotones and differentiated low-carbon development pathways: a case study of inner Mongolia, China - Le Chen; Bingfeng Li; Changxin Liu (Energy and Buildings, 2026)

Crustal anisotropic velocity structure beneath California constrained by P and PmP traveltimes: Implications for fluid-promoted creeping along the central San Andreas Fault - Jing Chen; Tianjue Li; Xiao Xiao; Shucheng Wu; Yiming Bai; Guoxu Chen; Bingfeng Zhang; Mijian Xu; Ping Tong (Earth and Planetary Science Letters, 2026)

Global distribution of Synechococcus and its carbon fixation potential in the ocean under climate change - Xinyu Chen; Zhenyan Zhang; Bingfeng Chen; Meng Liu; Yuanchen Chen; Liwei Sun; Josep Penuelas; Haifeng Qian (Limnology and Oceanography, 2026)
Synechococcus , a key genus of marine cyanobacteria, plays a crucial role in global carbon fixation; however, its potential for carbon fixation under future climate change remains underexplored. Here, we utilize machine learning to analyze 689 Synechococcus reference genomes and 953 marine metagenomic samples, uncovering the global distribution of Synechococcus species and their carbon fixation genes. The abundance and carbon fixation potential of Synechococcus in the ocean are primarily driven by carbonate and dissolved oxygen concentrations; however, the highest levels are predominantly found in mid‐latitude and low‐latitude regions, respectively. This contrasting pattern can be attributed to the heterogeneity in carbon fixation potential among different Synechococcus species and their environmental adaptations. Without policy interventions, climate change is projected to decrease Synechococcus abundance by approximately 20% across roughly 25 million km 2 of the surface ocean, primarily in low‐latitude regions. Conversely, the abundance of genes related to carbon fixation in Synechococcus is projected to increase in 50.6% of surface ocean areas. Mitigating greenhouse gas emissions could help preserve current distribution patterns. These findings provide important insights for predicting the carbon fixation capacity and species distribution of marine ecosystems under climate change, along with their potential impacts.

Corrugated aerogel with directional channels for enhanced oil adsorption and emulsion purification - Yuan Wang; Dafan Chen; Bingfeng Li; Wenjun Zhang; Yiming Li (Journal of Hazardous Materials, 2026)

Structural heterogeneity and anisotropy beneath Myanmar: Insights into the complex deformation of the Indo-Burma subduction zone - Yiming Bai; Shengji Wei; Jing Chen; Tianjue Li; Bingfeng Zhang; Xiao Xiao; Shucheng Wu; Jiayuan Yao; Yu Wang; Ping Tong (Earth and Planetary Science Letters, 2026)

Resilience analysis of electric vehicle charging infrastructure: a Bayesian network approach - Ning Guo; Mengying Li; Zhe George Zhang; Xi Chen; Bingfeng Xie (Transportation Research Part D: Transport and Environment, 2026)

The role of artificial intelligence in advancing population-based cancer registration - Shuai Ding; Mingyuan Liu; Hao Wang; Cheng Song; Luyue Zhao; Zhihao Yang; Yue Wang; Yifan Wang; Haitao Cui; Zihao Liu; Dongrun Liu; Tomohiro Matsuda; et al. (Science Bulletin, 2026)

Potential of traditional Chinese medicine as an antibiotic alternative for mitigating antibiotic resistance: A case study of Tetrastigma hemsleyanum - Zhihan Yang; Bingfeng Chen; Qi Zhang; Xinyang Hu; Liwei Sun; Tao Lu; Liyue Zhu; Yunan Ma; Hongwei Zhong; Yinhua Ni; Haifeng Qian (Journal of Hazardous Materials, 2025)

Biodegradable hierarchical hydrogel cellulose membrane for viscous crude oil/water emulsion separation: Performance and mechanistic insights - Dafan Chen; Shideng Yuan; Bingfeng Li; Mutai Bao; Wenjun Zhang; Zhining Wang; Yiming Li (Chemical Engineering Journal, 2025)

Different effects of heterocyclic compounds on the diversity and functions of soil microbiota - Wenying Ding; Bingfeng Chen; Minglong Song; Meng Liu; Binghai Lv; Danyan Qiu; Yuke Zhu; Zhenyan Zhang; Mengwei Zhang; Rongshe Zhang; Tao Lu; Haifeng Qian (Journal of Hazardous Materials, 2025)

Structural Effect of Pesticides on Rhizosphere Microbiome - Yitian Yu; Qi Zhang; Zhenyan Zhang; Nuohan Xu; Bingfeng Chen; Binghai Lv; Liwei Sun; Dong Zhu; Haifeng Qian; Tao Lu (Environmental Microbiology, 2025)
Pesticide residues in the field pose significant risks to nontarget organisms, and their structures determine their environmental behaviour. However, the effects of different pesticide structures on rhizosphere microbial function remain unclear. Herein, the effects of nine pesticides with sulfonylurea, carbamate and pyrethroid motifs on the wheat rhizosphere microbiome were investigated, revealing the potential mechanisms of ecological risk accumulation. The inhibitory effects of the sulfonylurea motif on microbial diversity were 6 and 19 times those of the other two pesticides, and the carbamate motif disrupted rhizosphere community stability. In addition, the sulfonylurea and carbamate motifs induced 0.3‐fold increases in antibiotic resistance genes compared to the control. The adverse effects of the pyrethroid motif were milder than those of the other two motifs in all assessments. With distinct structural effects, we identified key taxa that responded to these motifs, not only having the degrading potential function to specific pesticides but also contributing to the ecological risk accumulation in the rhizosphere. Our findings provide new evidence that structural motif‐specific induction of antibiotic resistance genes contributes to increased ecological risks from pesticide exposure.

The combination of microplastics and glyphosate affects the microbiome of soil inhabitant Enchytraeus crypticus - Huihui Yang; Guogang Zheng; Guoyan Qin; Qi Zhang; Ziyao Zhang; Bingfeng Chen; Chaotang Lei; Meng Liu; Rui Cui; Liwei Sun; Shengjie Xia; W.J.G.M. Peijnenburg; et al. (Journal of Hazardous Materials, 2025)

A new CNN-GRU deep learning framework optimized by CHIO for precise prediction of debris flow velocity - Liangxu Shen; Tianxing Ma; Hao Chen; Bingfeng Ye; Rui Luo; Hongyue Sun (Stochastic Environmental Research and Risk Assessment, 2025)

Lifetime probabilities of developing and dying from cancer in China: comparison with Japan and the United States in 2022 - Qian Zhu; Yifei Yao; Ru Chen; Bingfeng Han; Shaoming Wang; Li Li; Kexin Sun; Rongshou Zheng; Wenqiang Wei (Science China Life Sciences, 2025)

Developing a new index with time series Sentinel-2 for accurate tidal flats mapping in China - Ying Chen; Jinyan Tian; Jie Song; Wei Chen; Bingfeng Zhou; Xinyuan Qu; Liyan Zhang (Science of The Total Environment, 2025)

The effects of different halogenated-pyrethroid pesticides on soil microbial community - Binghai Lv; Zhenyan Zhang; Bingfeng Chen; Siqi Yu; Minglong Song; Yitian Yu; Tao Lu; Liwei Sun; Haifeng Qian (Science of The Total Environment, 2025)

Selective surface passivation of gold nanoparticles: A strategy for enhanced sensitivity in lateral flow immunoassay - Zongyou Chen; Sha Yu; Shijin Huang; Wei Zhang; Ping Guo; Juan Peng; Yonghua Xiong; Bingfeng Ma; Weihua Lai (Chemical Engineering Journal, 2025)

GLP-1 signaling-regulated SNAP25 is involved in improved insulin secretion in diabetic GK rats after Roux-en-Y gastric bypass surgery - Xiangchen Kong; Chao Lin; Chenxi Yang; Xin Wang; Bingfeng Li; Dan Yan; Yanhui Yang; Anyi Hu; Yanyin Chen; Xiaohui Xu; Xiaosong Ma (Molecular Biology Reports, 2024)

Integrating Anthropogenic–Pesticide Interactions Into a Soil Health‐Microbial Index for Sustainable Agriculture at Global Scale - Nuohan Xu; Bingfeng Chen; Yan Wang; Chaotang Lei; Zhenyan Zhang; Yangqing Ye; Mingkang Jin; Qi Zhang; Tao Lu; Huaping Dong; Jianxin Shou; Josep Penuelas; et al. (Global Change Biology, 2024)
Soil microbiota in intensive agriculture are threatened by pesticides, economic activities, and land‐use changes. However, the interactions among these anthropogenic factors remain underexplored. By analyzing 2356 soil metagenomes from around the world, we developed a comprehensive soil health‐microbial index that integrates microbial diversity, nutrient cycling potential, metabolic potential, primary productivity, and health risks to assess how the soil microbiota respond to anthropogenic factors. Our results indicated that the health‐microbial index was the lowest with severe pesticide contamination. Pesticides, in combination with other anthropogenic and climatic factors, exacerbate the decline in this index. Machine learning predictions suggest that the health‐microbial index in approximately 26% of global farmland could decline between 2015 and 2040, even under sustainable development scenarios. Even with strategies to reduce pesticide usage, we cannot completely halt the decline in the health‐microbial index. Our findings highlight that sustaining soil microbial health on a global scale requires addressing not only pesticide management but also broader anthropogenic impacts.

Long Non-Coding RNA PCAT19 Suppresses Cell Proliferation and Angiogenesis in Coronary Artery Disease through Interaction with GCNT2 - Yuan Zhou; Lei Zhang; Jiongchao Guo; Min Chen; Huangsheng Zheng; Bingfeng Zhou (Cell Biochemistry and Biophysics, 2024)

Integration of a biocompatible metal-phenolic network and fluorescence microspheres as labels for sensitive and stable detection of carbendazim with a lateral flow immunoassay - Zongyou Chen; Yanyan Tang; Ping Guo; Wei Zhang; Juan Peng; Yonghua Xiong; Bingfeng Ma; Weihua Lai (Food Chemistry, 2024)

Comprehensive reutilization of Glycyrrhiza uralensis residue by extrusion-biological pretreatment for coproduction of flavonoids, cellulase, and ethanol - Siyuan Chang; Chenke Yun; Bingqian Yang; Jinao Duan; Tianyi Chen; Lei Liu; Bingfeng Li; Sheng Guo; Sen Zhang (Bioresource Technology, 2024)

Effects of different assembly strategies on gene annotation in activated sludge - Meng Liu; Nuohan Xu; Bingfeng Chen; Zhenyan Zhang; Xinyu Chen; Yuke Zhu; Wenjie Hong; Tingzhang Wang; Qi Zhang; Yangqing Ye; Tao Lu; Haifeng Qian (Environmental Research, 2024)

Ultra-thin layer HTaMoO6 catalyst for the upgrading of carbohydrates into 5-hydroxymethylfurfural - Lei Zhang; Bingfeng Chen; Ti Zhou; Xiaomeng Cheng; Minghua Dong; Ye Liu; Huizhen Liu; Qingling Xu; Buxing Han (Chemical Engineering Journal, 2024)

Optimized DLP 3D-printed high-resolution nano zirconia-hydroxyapatite scaffold with craniomaxillofacial soft tissue invasion resistance and pro-osteogenic properties via dectin-1/syk inflammatory axis - Xiaomeng Gao; Jieting Yang; Xuejing Gan; Yixiong Lin; Jieyun Xu; Zhengjie Shan; Zongpu Han; Shijie Chen; Baoxin Huang; Bingfeng Fan; Zetao Chen (Chemical Engineering Journal, 2024)

Phages in different habitats and their ability to carry antibiotic resistance genes - Yan Wang; Zhenyan Zhang; Jian Kang; Bingfeng Chen; Wenjie Hong; Binghai Lv; Tingzhang Wang; Haifeng Qian (Journal of Hazardous Materials, 2024)

Metagenomic analysis of antibiotic-resistance genes and viruses released from glaciers into downstream habitats - Yan Wang; Nuohan Xu; Bingfeng Chen; Zhenyan Zhang; Chaotang Lei; Qi Zhang; Yanpeng Gu; Tingzhang Wang; Meixia Wang; Josep Penuelas; Haifeng Qian (Science of The Total Environment, 2024)

A global atlas of marine antibiotic resistance genes and their expression - Nuohan Xu; Danyan Qiu; Zhenyan Zhang; Yan Wang; Bingfeng Chen; Qi Zhang; Tingzhang Wang; Wenjie Hong; Ning-Yi Zhou; Josep Penuelas; Michael Gillings; Yong-Guan Zhu; et al. (Water Research, 2023)

Improving nutrients removal of Anaerobic-Anoxic-Oxic process via inhibiting partial anaerobic mixture with nitrite in side-stream tanks: Role of nitric oxide - Shuhan Lei; Ju Zhang; Bo Hu; Junkai Zhao; Wenjuan Yang; Bingfeng Shi; Ying Chen; Jianqiang Zhao (Bioresource Technology, 2023)

Global distribution of marine microplastics and potential for biodegradation - Bingfeng Chen; Zhenyan Zhang; Tingzhang Wang; Hang Hu; Guoyan Qin; Tao Lu; Wenjie Hong; Jun Hu; Josep Penuelas; Haifeng Qian (Journal of Hazardous Materials, 2023)

Metatranscriptome deciphers the effects of non-antibiotic antimicrobial agents on antibiotic resistance and virulence factors in freshwater microcosms - Yan Wang; Kepin Ni; Zhenyan Zhang; Nuohan Xu; Chaotang Lei; Bingfeng Chen; Qi Zhang; Liwei Sun; Yiling Chen; Tao Lu; Haifeng Qian (Aquatic Toxicology, 2023)

Pyrolysis temperature affects the physiochemical characteristics of lanthanum-modified biochar derived from orange peels: Insights into the mechanisms of tetracycline adsorption by spectroscopic analysis and theoretical calculations - Zhihao Chen; Bingfeng Lin; Yingping Huang; Yanbiao Liu; Yonghong Wu; Rui Qu; Cilai Tang (Science of The Total Environment, 2023)

Nano-Sized Polystyrene at 1 mg/L Concentrations Does Not Show Strong Disturbance on the Freshwater Microbial Community - Zhenyan Zhang; Meng Zheng; Bingfeng Chen; Yizhou Pan; Zhihan Yang; Haifeng Qian (Bulletin of Environmental Contamination and Toxicology, 2021)

Multi-GNSS precise point positioning (MGPPP) using raw observations - Teng Liu; Yunbin Yuan; Baocheng Zhang; Ningbo Wang; Bingfeng Tan; Yongchang Chen (Journal of Geodesy, 2017)